The relationship of gross upper and lower limb motor competence to measures of health and fitness in adolescents aged 13–14 years. Issue 1 (8th March 2018) - Weedon, Benjamin David; Liu, Francesca; Mahmoud, Wala; Metz, Renske; Beunder, Kyle; Delextrat, Anne; Morris, Martyn G; Esser, Patrick; Collett, Johnny; Meaney, Andy; Howells, Ken; Dawes, Helen
Abstract : Introduction: Motor competence (MC) is an important factor in the development of health and fitness in adolescence. Aims: This cross-sectional study aims to explore the distribution of MC across school students aged 13–14 years old and the extent of the relationship of MC to measures of health and fitness across genders. Methods: A total of 718 participants were tested from three different schools in the UK, 311 girls and 407 boys (aged 13–14 years), pairwise deletion for correlation variables reduced this to 555 (245 girls, 310 boys). Assessments consisted of body mass index, aerobic capacity, anaerobic power, and upper limb and lower limb MC. The distribution of MC and the strength of the relationships between MC and health/fitness measures were explored. Results: Girls performed lower for MC and health/fitness measures compared with boys. Both measures of MC showed a normal distribution and a significant linear relationship of MC to all health and fitness measures for boys, girls and combined genders. A stronger relationship was reported for upper limb MC and aerobic capacity when compared with lower limb MC and aerobic capacity in boys (t=−2.21, degrees of freedom=307, P=0.03, 95% CI −0.253 to –0.011). Conclusion: Normally distributed measures of upper and lower limb MC are linearly related to health and fitness measures in adolescents in a UK sample. Trial registration number: NCT02517333 .